Role of Ectomycorrhizal Symbiosis Behind the Host Plants Ameliorated Tolerance Against Heavy Metal Stress - Chot, Eetika; Reddy, Mondem Sudhakara (Frontiers in Microbiology, 2022)
Soil heavy metal (HM) pollution arises from natural and anthropogenic sources, is a prime threat to the environment due to its accumulative property and non-biodegradability. Ectomycorrhizal (ECM) symbiosis is highly efficient in conferring enhanced metal tolerance to their host plants, enabling their regeneration on metal-contaminated lands for bioremediation programs. Numerous reports are available regarding ECM fungal potential to colonize metal-contaminated lands, various defense mechanisms of ECM fungi and plants against HM stress separately. To utilize ECM-plant symbiosis successfully for bioremediation of metal-contaminated lands, understanding the fundamental regulatory mechanisms through which ECM symbiosis develops an enhanced metal tolerance in their host plants has prime importance. As this field is highly under-studied, the present review emphasizes how plants' various defense systems and their nutrient dynamics with soil are impacted by ECM fungal symbiosis under metal stress, ultimately leading to their host plants ameliorated tolerance and growth. Overall, we conclude that ECM symbiosis improves the plant growth and tolerance against metal stress by i) preventing their roots direct exposure to toxic soil heavy metals, ii) improving plant antioxidant activity and intracellular metal sequestration potential, and iii) altering plant nutrient uptake from the soil in such a way to enhance their tolerance against metal stress. In some cases, ECM symbiosis promotes HM accumulation in metal stressed plants simultaneous to improved growth under the HM dilution effect.